Health Counseling About Anemia With Educational Videos for Adolescent Women at 2nd Junior High School Sewon Bantul (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Adolescent girls are one of the groups that are prone to anemia due to menstruation so they need nutritional intake in the form of iron to produce hemoglobin in the body to replace menstrual blood lost every month. Adolescent girls have a ten times higher risk of experiencing anemia compared to adolescent boys. The reason is because adolescent girls menstruate every month and are growing, so they need a greater intake of iron. Daily eating habits are greatly influenced by knowledge, and one of the factors that influences adolescent eating habits is the level of knowledge. The aim of this education for adolescents is to increase knowledge and skills in maintaining adolescent health. The activity was carried out on July 19th, 2024. The target of this activity was students in grades eight with a total of 30 participants. The activity was carried out using a counseling method through educational videos. In community service using the counseling method with educational video media, it shows the results of the benefits in providing education and instructions on anemia to young women. The results show that teenagers gain an understanding of anemia, showing how important it is to provide information about anemia to teenagers. the health education method with video media is more effective in influencing someone's understanding, especially in adolescents, of anemia.